2014
DOI: 10.1159/000359960
|View full text |Cite
|
Sign up to set email alerts
|

On Some Quantitative Properties of Czech ř in Newsreading

Abstract: This research examines the distributional characteristics of Czech ř in terms of the number of contacts (periods). The traditional claim that this consonant is produced with two or more contacts is challenged by the empirical evidence of ř realized in connected speech (newsreading style). The results of the study show that the most common variant of the (ř) variable is a one-contact alveolar sound, with the multiple-contact realization of ř being extremely rare. The role of eight linguistic variables is assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Based on the similarity, Howson et al (2015) suggested that the degree of grooving generates acousticperceptual similarities in the frication produced by the two segments. One of the primary points of contrast between /r̝, ʒ/ is trilling, which is often lost during casual speech (Pavlík, 2013). While this may generally play a role in their perceptual confusability, we ensured that the tokens used in the current experiment contained trilling.…”
Section: Discussion Of Czech Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the similarity, Howson et al (2015) suggested that the degree of grooving generates acousticperceptual similarities in the frication produced by the two segments. One of the primary points of contrast between /r̝, ʒ/ is trilling, which is often lost during casual speech (Pavlík, 2013). While this may generally play a role in their perceptual confusability, we ensured that the tokens used in the current experiment contained trilling.…”
Section: Discussion Of Czech Resultsmentioning
confidence: 99%
“…Previous acoustic studies have described the trill-fricative as having 1-2 times more tongue-palate contacts than /r/, which vibrates 1-3 times (Dankovičová, 1997), although it has been noted that the Czech trill-fricative is not always trilled, and its realization is contextually dependant (Pavlík, 2013). The trillfricative induces a much higher spectral tilt on adjacent vowels and a lower F1 compared to the trill, indicating a more open glottal state consistent with breathy voice during production the trill-fricative (Howson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%